Unusual fan shaped ossification in a female fetus with radiological features of boomerang dysplasia. Issue 4 (1st April 1999) - Odent, Sylvie; Loget, Philippe; Le Marec, Bernard; Delezoïde, Anne-Lise; Maroteaux, Pierre
Abstract : We report on a female fetus of 24 weeks whose clinical and radiological findings were compatible with boomerang dysplasia (BD). However, histopathology was unusual with a lateral fan shaped diaphyseal ossification. This has never been described either in typical atelosteogenesis I (AT-I) or in BD. The purpose of this report is to find out if this condition is a separate lethal bone dysplasia or another histological feature of the nosological group of AT-I and BD.